2018
DOI: 10.1002/sd.1851
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitanism and ethical consumption: An extended theory of planned behavior and modeling for fair trade coffee consumers in South Korea

Abstract: To better understand consumers' fair trade purchasing intentions, this study proposed an extended model of the Theory of Planned Behavior (TPB) in which a new determinant, cosmopolitanism, was added to reflect consumers' global orientation and perception of fair trade coffee in the context of globalization. In addition, this study employed the construct of “purchase implementation intention” to address the gap between stated intention and actual behavior. To test the study's hypotheses, a random survey was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 77 publications
2
28
0
Order By: Relevance
“…In particular, sustainability scholars have found that the TPB model helps explain consumer behavior in terms of the adoption of agri‐environmental innovations (Caffaro, Roccato, Micheletti Cremasco, & Cavallo, 2019), cross‐cultural sustainable consumption (Ceglia, de Oliveira Lima, & Leocádio, 2015), and residents' participation in sustainable development (Hao et al, 2020). Furthermore, the use of an ETPB on sustainable development has been found to successfully predict ethical consumption behavior and cosmopolitanism (Lee, Jin, & Shin, 2018). Due to the significance of the ETPB in crowdfunding, this study attempts to examine funder behavior using the ETPB and theories of constraints and attachment style in the context of sustainability crowdfunding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, sustainability scholars have found that the TPB model helps explain consumer behavior in terms of the adoption of agri‐environmental innovations (Caffaro, Roccato, Micheletti Cremasco, & Cavallo, 2019), cross‐cultural sustainable consumption (Ceglia, de Oliveira Lima, & Leocádio, 2015), and residents' participation in sustainable development (Hao et al, 2020). Furthermore, the use of an ETPB on sustainable development has been found to successfully predict ethical consumption behavior and cosmopolitanism (Lee, Jin, & Shin, 2018). Due to the significance of the ETPB in crowdfunding, this study attempts to examine funder behavior using the ETPB and theories of constraints and attachment style in the context of sustainability crowdfunding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory of planned behavior (TPB) model (Ajzen, 1991) consists of three focal components: attitude, subjective norms, and perceived behavioral control. Numerous studies have applied this theoretical TPB model to explore consumers' willingness to participate in certain pro‐environmental behaviors (e.g., Bamberg, Ajzen, & Schmidt, 2003; Bamberg & Schmidt, 2001; Chen, 2016; Lam, 1999; Terry, Hogg, & White, 1999) and purchase behavior of environmentally sustainable products (Kumar, Manrai, & Manrai, 2017; Lee, Jin, & Shin, 2018). In addition, a meta‐analysis conducted by Nardi, Jardim, Ladeira, and Santini (2019) had verified that the application of the TPB model is robust to predict food choice.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasingly more people, organisations and institutions, which alert about the risks of economic and consumption models that advocate an intensive use of resources (Chen et al, 2016; Fellner & Goehmann, 2020; Goyes & Sollund, 2018; Mikulčić et al, 2020; Zasada et al, 2020). In this sense, a consumption trend, which seems to follow more ethical and sustainable behaviour patterns has been noted in recent years (Chatzidakis et al, 2016; Lee et al, 2018; Rousseau, 2015). However, the market share, which this segment represents is still very small compared with that of traditional basic products (Brunner, 2014; Schollenberg, 2012).…”
Section: Introductionmentioning
confidence: 71%